2013
DOI: 10.1149/05810.0183ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Catalytic Surface Reactions during Nucleation and Growth of Atomic Layer Deposition of Noble Metals: A Case Study for Platinum

Abstract: Atomic layer deposition (ALD) of noble metals has attracted much attention in recent years for the deposition of thin metal films, as well as for the synthesis of supported metallic nanoparticles. Noble metal surfaces and nanoparticles possess catalytic activity for dissociation of metalorganic precursor and O 2 molecules, which has important consequences for the reaction mechanisms of ALD. In this work, a case study is presented with respect to the importance of catalytic surface reactions during the nucleati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For Pt ALD, the reaction mechanism of film growth is strongly dependent on catalytic surface reactions [38]. During the MeCpPtMe 3 pulse of the ALD process, the ligands of the MeCpPtMe 3 precursor undergo dehydrogenation reactions on the catalytic Pt surface, [20] which leads to a surface covered with carbonaceous species [39].…”
Section: Catalytic Surface Reactions During Nanoparticle Growthmentioning
confidence: 99%
“…For Pt ALD, the reaction mechanism of film growth is strongly dependent on catalytic surface reactions [38]. During the MeCpPtMe 3 pulse of the ALD process, the ligands of the MeCpPtMe 3 precursor undergo dehydrogenation reactions on the catalytic Pt surface, [20] which leads to a surface covered with carbonaceous species [39].…”
Section: Catalytic Surface Reactions During Nanoparticle Growthmentioning
confidence: 99%
“…Most of these processes use molecular oxygen (O 2 ), a reactant that is otherwise usually found to be inert under typical ALD conditions, to combust ligands of the metal precursors. Successful use of molecular oxygen relies on its dissociative adsorption on catalytically active platinum-metal surfaces, transforming it into the much more reactive atomic form. , Most of the ALD studies on platinum metals have concerned platinum and ruthenium (see ref for a thorough review on platinum-metal ALD), whereas iridium has gained less attention despite its attractive properties such as high melting point, high density, low electrical resistivity, and excellent chemical resistance . Previously reported ALD processes of Ir most often use O 2 as a reactant with Ir­(acac) 3 , , (EtCp)­Ir­(COD), or (MeCp)­Ir­(CHD) at temperatures above 200 °C, whereas consecutive O 3 and H 2 pulses can be used to deposit Ir at temperatures below 200 °C. , Plasma-enhanced ALD processes using H 2 plasma, NH 3 plasma, or mixed O 2 –H 2 plasma have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2B, during precursor pulse, the [50] and Medlin et al [51] suggested that the OH group on metal oxides play a significant role in the nucleation of Pt atoms. There are several processes that may play a role in the nucleation stage ( Figure 3A) [52,53]: (i) atom diffusion; (ii) particle ripening/Ostwald ripening and (iii) spillover of species from the NPs. Pt nanoparticle formed via an island growth mechanism (Volmer-Weber mechanism) during the initial stages of ALD process, followed by island coalescence and formation of a continuous thin film as shown in Figure 3B.…”
Section: The Mechanism Of Ald Pt Processmentioning
confidence: 99%